Considerations for the Optimization of Induced White Matter Injury Preclinical Models - Ahmad, Abdullah Shafique; Satriotomo, Irawan; Fazal, Jawad; Nadeau, Stephen E.; Doré, Sylvain (Frontiers in Neurology, 2015)
The white matter injury in relation to acute neurologic conditions, especially stroke, has remained obscure until recently. Current advances in the imaging technologies in the field of stroke have confirmed that white matter injury plays an important role in the prognosis of stroke and suggest that white matter protection is essential for functional recovery and post-stroke rehabilitation. However, due to the lack of a reproducible animal model of white matter injury, the pathophysiology and mechanisms of this injury are not well studied. Moreover, producing selective white matter injury in animals, especially in rodents, has proven to be challenging. Problems associated with inducing selective white matter ischemic injury in the rodent derive from differences in the architecture of the brain, most particularly the ratio of white matter to gray matter in rodents compared to humans, the agents used to induce the injury, and the location of the injury. Aging, gender differences, and comorbidities further add to this complexity. This review provides a brief account of the techniques commonly used to induce general white matter injury in animal models (stroke and non-stroke related) and highlights relevance, optimization issues, and translational potentials associated with this particular form of injury.